Supporting Factors for Student Compliance in Islamic Boarding Schools - Rahmatan Azzahra; Nurus Sa’adah (Civiliza Publishing, Indonesia., 2026)
Students' compliance with discipline is an important indicator of the success of character education in Islamic boarding schools, but the challenge of obedience arises when adolescent students who have a desire for freedom must adapt to the strict rules of the Islamic boarding school. This study aims to identify and analyze the factors that support the compliance of students in Islamic boarding schools through psychological, social, and institutional perspectives. The research method uses literature studies by collecting and studying various relevant literature in the form of journal articles, books, and research reports related to student compliance and pesantren education. The analysis was carried out by grouping information based on key themes and identifying patterns of relationships between factors. The results of the study show three categories of factors supporting student compliance: (1) internal factors including self-control, social support, emotional intelligence, self-adjustment, and religiosity that form the psychological foundation of students; (2) external factors include peer influence and the role of ustadz/kyai as authority figures who provide examples; (3) institutional factors in the form of pesantren education methods which include uswah hasanah, discipline, habituation, and advice that form a systematic habitus of obedience. These three factors interact with each other and strengthen in forming holistic and sustainable student compliance. Research recommendations include the development of self-control and emotional intelligence training programs, the creation of a supportive environment through a structured mentoring system, the strengthening of ustadz pedagogical competence, and the innovation of educational methods that are adaptive but still maintain the traditional values of pesantren to optimize the formation of the character of students who are obedient, independent, and have noble character.